Cost-effectiveness analysis of 10- and 13-valent pneumococcal conjugate vaccines in Peru. (7th May 2015) - Mezones-Holguin, Edward; Canelo-Aybar, Carlos; Clark, Andrew David; Janusz, Cara Bess; Jaúregui, Bárbara; Escobedo-Palza, Seimer; Hernandez, Adrian V.; Vega-Porras, Denhiking; González, Marco; Fiestas, Fabián; Toledo, Washington; Michel, Fabiana; et al.
Highlights: Pneumococcal conjugate vaccines (PCV) help to prevent pneumococcal diseases (PD). PCV13 reduces more cases of severe PD, deaths and sequelae than PCV10. PCV10 prevents more AOM cases than PCV13. Separately, both PCV13 and PCV10 showed to be cost-effective in Peru. Overall, PCV13 is more cost-effective than PCV10 for the Peruvian context, showing an extended dominance. Abstract: Objective: To evaluate the cost-effectiveness of introducing the 10-valent pneumococcal conjugate vaccine (PCV10) versus the 13-valent PCV (PCV13) to the National Immunization Schedule in Peru for prevention of pneumococcal disease (PD) in children <5 years of age. Methods: The integrated TRIVAC vaccine cost-effectiveness model from the Pan American Health Organization's ProVac Initiative (version 2.0) was applied from the perspective of the Government of Peru. Twenty successive cohorts of children from birth to 5 years were evaluated. Clinical outcomes were pneumococcal pneumonia (PP), pneumococcal meningitis (PM), pneumococcal sepsis (PS) and acute otitis media from any causes (AOM). Measures included prevention of cases, neurological sequelae (NS), auditory sequelae (AS), deaths and disability adjusted life years (DALYs). A sensitivity analyses was also performed. Findings: For the 20 cohorts, net costs with PCV10 and PCV13 were US 363.26 million and US 408.26 million, respectively. PCV10 prevented 570, 273 AOM; 79, 937 PP; 2217 PM; 3049 PS; 282 NS; 173 AS; and 7512 deaths. PCV13 prevented 419, 815 AOM; 112, 331 PN; 3116 PM; 4285 PS; 404 NS; 248 AS; and 10, 386 deaths. Avoided DALYs were 226, 370 with PCV10 and 313, 119 with PCV13. Saved treatment costs were US 37.39 million with PCV10 and US 47.22 million with PCV13. Costs per DALY averted were US 1605 for PCV10, and US 1304 for PCV13. Sensitivity analyses showed similar results. PCV13 has an extended dominance over PCV10. Conclusion: Both pneumococcal vaccines are cost effective in the Peruvian context. Although the net cost of vaccination with PCV10 is lower, PCV13 prevented more deaths, pneumococcal complications and sequelae. Costs per each prevented DALY were lower with PCV13. Thus, PCV13 would be the preferred policy; PCV10 would also be reasonable (and cost-saving relative to the status quo) if for some reason 13-valent were not feasible.